A prospective comparative study to evaluate the efficacy and safety of olopatadine eye drops and bepotastine eye drops in subjects of vernal kerato conjunctivitis - Malahat, Amatur R.; Kodudula, Sudhakar; Gali, Vijaya L. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Vernal keratoconjunctivitis (VKC) is an allergic eye disease that especially affects young boys. Both olopatadine and bepotestine are dual acting drugs that provide rapid symptomatic relief coupled with the long-term disease-modifying benefit. The present study is conducted to compare the efficacy and safety of olopatadine eye drops and bepotastine eye drops in patients of vernal keratoconjunctivitis. Methods: A prospective, randomized, parallel-group, comparative study is conducted over a period of 4 weeks on paediatric patients with VKC. 50 patients are recruited and randomized into two treatment groups. They received the assigned drugs for 4 weeks and are called for follow up at the end of 1st week, 4th week and 12th week. At each follow-up, patients are examined and the clinical parameters are graded. Results: This study shows that both olopatadine and bepotastine are equally efficacious. Bepotastine provided quicker relief to symptoms of watering, ocular discomfort and conjunctival hyperaemia. Number of responders are also more in the bepotastine group. Absolute eosinophilic count improved with both the drugs but there is no statistically significant difference between them. Both drugs showed good safety profile. However, 24% patients reported aversion to bitter taste with bepotastine. There is no treatment related severe adverse effects in both the groups. Conclusions: Both olopatadine and bepotastine are effective in treating vernal keratoconjunctivitis. However, bepotastine performed better in reducing tearing, ocular discomfort and conjunctival hyperaemia.